Informal knowledge transfer in the period before formal health education programmes: case studies of mass media coverage of HIV and SIDS in England and Wales - Pashayan Nora; Jenkins Rebeka; Hilliard Nick; Powles John (BMC, 2007)
Abstract Background How advances in knowledge lead via behaviour change to better health is not well understood. Here we report two case studies: a rapid reduction in HIV transmission in homosexual men and a decline in Sudden Infant Death Syndrome (SIDS) that took place in the period before the relevant national education programmes commenced, respectively, in 1986 and 1991. The role of newspapers in transferring knowledge relevant to reducing the risk of AIDS and SIDS is assessed. Methods HIV Searches were made of The Times (1981-1985), Gay News (1981-1984) and, for the key period of April to June 1983, of eight newspapers with the highest readership. Information on transmission route and educational messages were abstracted and analysed. SIDS Searches were made of The Times and the Guardian (1985-1991), The Sun (selected periods only, 1988-1991) and selected nursing journals published in England and Wales. Information on sleeping position and educational messages were abstracted and analysed. Results HIV Forty-five out of 50 articles identified in newspapers described homosexuals as an at risk group. Sexual transmission of AIDS was, however, covered poorly, with only 7 (14%) articles referring explicitly to sexual transmission. Only seven articles (14%) associated risk with promiscuity. None of the articles were specific about changes in behaviour that could be expected to reduce risk. Gay periodicals did not include specific advice on reducing the number of partners until early 1984. SIDS Out of 165 relevant articles in The Times and 84 in the Guardian, 7 were published before 1991 and associated risk with sleeping position. The reviewed nursing journals reflected a pervasive sense of uncertainty about the link between SIDS and sleeping position. Conclusion Presumptively receptive audiences responded rapidly to new knowledge on how changes in personal behaviour might reduce risk, even though the 'signals' were not strong and were transmitted, at least partly, through informal and 'horizontal' channels. Advances in knowledge with the potential to prevent disease by behaviour change may thus yield substantial health benefits even without the mediation of formal education campaigns ('interventions'). Formal campaigns, when they came, did make important additional contributions, especially in the case of SIDS.